2018
DOI: 10.1002/mrm.27584
|View full text |Cite
|
Sign up to set email alerts
|

Fast and sensitive dynamic oxygen‐enhanced MRI with a cycling gas challenge and independent component analysis

Abstract: Purpose There is a critical need for non‐invasive imaging biomarkers of tumor oxygenation to assist in patient stratification and development of hypoxia targeting therapies. Using a cycling gas challenge and independent component analysis (ICA), we sought to improve the sensitivity and speed of existing oxygen enhanced MRI (OE‐MRI) techniques to detect changes in oxygenation with dynamically acquired T1W signal intensity images (dOE‐MRI). Methods Mice were implanted with SCCVII, HCT‐116, BT‐474, or SKOV3 tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…[13][14][15][16][17][18] (2) Verification that the distribution of hypoxic and normoxic areas seen with OE-MRI display intratumoural heterogeneity but with spatially coherent regions in keeping with patterns known to occur biologically. 5,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (3) Correlation against histopathological hypoxia indicators such as pimonidazole staining, glucose transporter 1 (GLUT-1) expression and hypoxia-inducible factor 1-α (HIF-1α) expression. 17,29,31,32,34-38 (4) Verification of OE-MRI's ability to predict tumours more likely to display hypoxia induced treatment resistance.…”
Section: Research Focusmentioning
confidence: 99%
“…[13][14][15][16][17][18] (2) Verification that the distribution of hypoxic and normoxic areas seen with OE-MRI display intratumoural heterogeneity but with spatially coherent regions in keeping with patterns known to occur biologically. 5,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (3) Correlation against histopathological hypoxia indicators such as pimonidazole staining, glucose transporter 1 (GLUT-1) expression and hypoxia-inducible factor 1-α (HIF-1α) expression. 17,29,31,32,34-38 (4) Verification of OE-MRI's ability to predict tumours more likely to display hypoxia induced treatment resistance.…”
Section: Research Focusmentioning
confidence: 99%
“…OE-MRI does not provide quantitative measures of oxygen per se but maps oxygen delivery in tissues with fully saturated haemoglobin [423,424]. Its potential was assessed in preclinical studies, in healthy individuals subjected to respiratory challenges and in patients with lung cancer and advanced cancer of the abdomen and pelvis [425][426][427].…”
Section: Techniques To Map Hypoxic Areas and Immune Infiltrationmentioning
confidence: 99%
“…53 Preclinical and clinical studies have demonstrated that the volume of oxygenrefractory voxels can be used to map and quantify hypoxic fractions across a range of tumour types. [54][55][56][57] OE-MRI revealed extensive tumour subregions that were refractory to oxygeninduced signal intensity changes in a syngeneic rat rhabdomyosarcoma model, again consistent with the presence of hypoxia. 49,50 Preliminary OE-MRI investigations in RH41 rhabdomyosarcoma xenografts also suggest a strong hypoxia signature in this tumour type ( Fig.…”
Section: Hypoxia Imagingmentioning
confidence: 52%